Nickel sulfide-based composite as electrodes in electrochemical sensors: A review - Irandoost, Maryam; Kumari, Beena; Truong, Tuyen; Karki, Bhishma; Miah, Md Rahimullah (Journal of Composites and Compounds, 2023)
Nickel sulfide (NiS) is an extremely a transition metal sulfide with great potential use as a sensor material because of its exceptional conductivity and stability. Herein, we present first, the all of synthesis of NiS into sensor and biosensor. Electrochemical sensor, Due to the fact that disposal to electrolyte during electrochemical impact can rapidly deform NiS, lowering its electroactivity and measurement repeatability, a method for effectively integrating NiS into sensors is crucial. Then, the main focus of this review is the recent advancements in sensor systems that utilize NiS and its composites. The article discusses the correlation between sensing performance and electrode construction strategies, and identifies shortcomings and limitations in the current applications of these sensors. Based on this analysis, the authors suggest potential future directions and areas for further research in the development of NiS-based sensors. This study focused on developments in NiS-based sensor systems and their composites throughout the past articles. The article investigates the correlation between the way electrodes are made and the effectiveness of the sensors they produce. On this basis, we discuss the scope for future of NiS-based sensors and offer additional directions.